2008
DOI: 10.1101/gr.076166.108
|View full text |Cite
|
Sign up to set email alerts
|

Mapping translocation breakpoints by next-generation sequencing

Abstract: Balanced chromosome rearrangements (BCRs) can cause genetic diseases by disrupting or inactivating specific genes, and the characterization of breakpoints in disease-associated BCRs has been instrumental in the molecular elucidation of a wide variety of genetic disorders. However, mapping chromosome breakpoints using traditional methods, such as in situ hybridization with fluorescent dye-labeled bacterial artificial chromosome clones (BAC-FISH), is rather laborious and time-consuming. In addition, the resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(83 citation statements)
references
References 27 publications
1
78
0
4
Order By: Relevance
“…Palindromic AT-rich repeats on Chromosomes 3, 8, 11, 17, and 22 also generate recurrent translocations, the most common of which is the recurrent t(11;22) that causes Emanuel syndrome (Edelmann et al 2001;Kurahashi et al 2003;Gotter et al 2007;Kato et al 2012Kato et al , 2014. Most germline translocations, however, are not recurrent, and sequencing of translocation breakpoints has revealed features of nonhomologous end-joining (NHEJ) and microhomology-mediated break-induced replication (MMBIR) at more than 60 unique translocation junctions (Chen et al 2008;Higgins et al 2008;Sobreira et al 2011;Chiang et al 2012;Robberecht et al 2013). …”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Palindromic AT-rich repeats on Chromosomes 3, 8, 11, 17, and 22 also generate recurrent translocations, the most common of which is the recurrent t(11;22) that causes Emanuel syndrome (Edelmann et al 2001;Kurahashi et al 2003;Gotter et al 2007;Kato et al 2012Kato et al , 2014. Most germline translocations, however, are not recurrent, and sequencing of translocation breakpoints has revealed features of nonhomologous end-joining (NHEJ) and microhomology-mediated break-induced replication (MMBIR) at more than 60 unique translocation junctions (Chen et al 2008;Higgins et al 2008;Sobreira et al 2011;Chiang et al 2012;Robberecht et al 2013). …”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…The analysis of this intronic region shows repetitive elements such as AluY (CENSOR; Kohany et al, 2006; http://www.girinst.org/censor/index.php). Despite the resolution afforded by the Affymetrix array used here, the data do not enable any conclusion to be made regarding the mechanism of the translocation event, which is likely to involve non-homologous end-joining as opposed to non-allelic homologous recombination (Erdogan et al, 2006;Chen et al, 2008). …”
Section: Genetic Analysismentioning
confidence: 88%
“…Previous work has shown that paired-end mapping or mate pair sequencing has unprecedented resolution for the detection of SV breakpoints of balanced genomic rearrangements in patients with ID/MCA and may thus be a valuable tool for diagnostic implementation. [16][17][18][19][20][21][22][23] Here we made a systematic comparison between mate pair sequencing versus array CGH and karyotyping. As a first important conclusion from this work, we demonstrate that all types of pathogenic SVs previously found with array CGH or karyotyping could also be found using a combined strength of the cluster and DOC signatures of mate pair sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Korbel et al 15 were the first to use NGS to map structural variations in the human genome, and several other groups have used this technique to finemap the breakpoints of specific structural aberrations (mostly apparently balanced chromosomal aberrations) in patients with ID/MCA. [16][17][18][19][20][21][22][23] Therefore, the technique has proven its usability in characterizing individual SVs. Here we describe the first systematic comparison between mate pair sequencing, genomic microarrays and karyotyping in a large cohort of ID/MCA patients referred to our diagnostic departments.…”
Section: Introductionmentioning
confidence: 99%